Shaping the Vulnerable Self: Parent-Child Attachment, Neuroticism, and Depressive Symptoms among Chinese Emerging Adults - Du,Zheng (2026)
Mental health challenges among Chinese emerging adults have become an increasingly important public concern, yet the interplay between family relational environments and dispositional vulnerability remains insufficiently examined. Drawing on attachment theory, this study examines the direct and indirect relationships between perceived parent–child attachment quality, trait neuroticism, and depressive symptoms among Chinese emerging adults (aged 18–30). This study utilizes data from the 2018 wave of the China Family Panel Studies (CFPS) to evaluate a nationally representative sample of 4,102 respondents. These variables were captured using adapted versions of the Inventory of Parent and Peer Attachment (IPPA), CES-D 8, and Big Five Personality scale, with the model analyzed via structural equation modelling (SEM). The results showed that both attachment quality (β = −.11, p < .001) and neuroticism (β = .28, p < .001) independently predicted depressive symptoms, whereas the hypothesized mediation pathway was non-significant (95% CI [−.019, .071]). These findings indicate that parent-child attachment quality and neuroticism associate in parallel rather than sequentially with depressive symptoms. This suggests that neuroticism stabilizes as an internalized trait by emerging adulthood, while perceived attachment functions as a distinct external protective resource. These findings imply that mitigating depressive symptoms among Chinese emerging adults may require differentiated strategies: targeting neuroticism through cognitive-level interventions while simultaneously leveraging the modifiable protective potential of parent-child attachment quality.
Keywords: parent-child attachment quality; neuroticism; depressive symptoms; emerging adulthood; China; CFPS